Performance of PET and nano-silica modified stone mastic asphalt mixtures - Mashaan, Nuha S; Chegenizadeh, Amin; Nikraz, Hamid (Elsevier, 2022)
Stone mastic asphalt (SMA) has become widely used in the field of pavement engineering. Using specific additives in SMA is necessary due to climate change and load condition variations. Thus, it is essential to utilise a modern mixture with a high capacity to survive the high traffic loads. The current study aims to use a combination of waste polyethene terephthalate (PET) and Nano-silica (NS) as a newly developed hybrid additive in SMA modification to improve rutting and fatigue performance. Waste PET and NS were blended with the C320 bitumen binder by using the wet-mix process, producing SMA mixtures. The Nano-silica was added to the C320 binder (2%, 4%, 6% and 8% by weight of the binder). The engineering properties was assessed through the Marshall stability, wheel tracking test, indirect tensile strength ratio test, resilient modulus test, and drain-off tests. The results indicated that adding 4–8% of Nano-silica with 6% waste PET plastic improves the rutting performance, stiffness modulus, tensile strength ratio, and fatigue performance of the modified SMA mixtures in comparison to non-modified mixtures. The significant performance of rut depth and stiffness modulus, tensile strength ratio and drain-offs were recorded as 1.2 mm, 6100 MPa, 96.4%, and 0.04%, respectively. Results revealed that mixtures modified with the hybrid additive of 6%PET6%NS have superior performance concerning better stiffness and rutting resistance. The results showed that the increase in Nano-silica content with PET plastic increased the fatigue life to the highest extent, at up to 220,490, for the hybrid additive of 6PET6NS mixtures. Based on the results of rutting and fatigue performance, the hybrid additive of 6PET6NS mixtures reflects the optimum and ideal content. The results demonstrated that the inclusion of NS with PET successfully decreased the drain-off rates, increased the rutting resistance, and improved the fatigue life.